Significant Correlation Between Overall Survival and Mean Lung Dose in Lung Stereotactic Body Radiation Therapy (SBRT) - Dupic, Guillaume; Biau, Julian; Molnar, Ioana; Chassin, Vincent; Dedieu, Véronique; Lapeyre, Michel; Bellière-Calandry, Aurélie (Frontiers in Oncology, 2020)
Background After stereotactic body radiation therapy (SBRT) for medically inoperable stage I non-small-cell lung cancer (NSCLC), more patients die of comorbidities, particularly severe pulmonary insufficiency, than of tumor progression. The aim of this study was to evaluate correlation between lung biologically effective dose (BED) with an α/β ratio of 3 Gy (BED3) and overall survival (OS) for these patients. Methods From 2012 to 2017, we have developed a prospectively updated institutional database for all first 100 consecutively treated patients with inoperable Stage 1 (T1T2N0M0) NSCLC. All SBRT were conducted on a Novalis Tx® LINAC with two coplanar dynamic conformal arcs (84%) or with coplanar volumetric modulated arc therapy (VMAT) (16%). Mean GTV and PTV were 8.6 cc and 50.8 cc, respectively. The marginal dose prescribed to the PTV was the 80% isodose line (IDL), i.e., 54 Gy in 3 fractions for 76 patients (BED10 = 126 Gy) and 50 Gy in 5 fractions for 24 patients (BED10 = 83.3 Gy). Pulmonary heterogeneity has been taken into account by using Monte Carlo or AAA algorithms. Median follow-up was 25 months. Results At 1, 2, 3 and 5 years, local control (LC) was respectively 100, 98.2, 98.2, and 77.7%, and OS was respectively 83, 71.2, 58.1, and 33.2% (median OS was 49 months). Significant OS prognostic factors in univariate and multivariate analysis were mean lung BED3 (HR = 1.14, p = 0.01) and PTV volume (HR = 1.01, p = 0.004). A mean lung BED3 ≤ 5 Gy was significantly associated with a doubling of median OS from 29 months to more than 60 months (not achieved, p = 0.0068). For patients with a forced expiratory volume in 1 second (FEV1) ≤ 40%, a mean lung BED3 ≤ 4 Gy was significantly associated with a doubling of median OS from 23 to 46 months (p = 0.019). Conclusion Mean lung BED3 is strongly and significantly associated with OS in SBRT for inoperable Stage I NSCLC. For all treated patients, a mean lung BED3 ≤ 5 Gy lead to a doubling of median OS. This threshold value should be reduced to 4 Gy for patients with FEV1 ≤ 40%.